Lessons Learnt through Covid-19 Pandemic Crisis-strategies Used by Teachers in Training to Survive during the Pandemic - Constance Chifamba (Research Highlights in Language, Literature and Education Vol. 4, 2023)
This study explored the impact of Covid-19 Pandemic on the learning experiences of second year student-teachers during the Covid-19 Pandemic. A qualitative case study was carried out on seven purposively sampled student-teachers from a class of 55 at a University teachers-training Program. Online semi-structured interviews were used. Thematic data analysis was used. Results indicate that the student teachers experienced both negative and positive impacts of Covid-19 Pandemic. Negative effects included academic challenges due to learning gaps, financial and socio-emotional challenges. Based on Bandura’s Reciprocal Determinism Theory both students and lecturers had to adapt to their environment. The positive impacts include the shift to blended learning and integration of technology in the learning and assessment of teaching practice. Important lessons learnt include developing solidarity as exhibited through friendly networking among the students which kept most of them going because it gave them a sense of belonging and connection to others at their institution so they feel they have shared burdens and shared vision. Other lessons learnt were disaster preparedness and prioritizing education. The study recommends that everyone should be a life-long learner, develop flexibility as well as resilience as key tools to face a crisis.